Proteus mirabilis Vesicles Induce Mitochondrial Apoptosis by Regulating miR96-5p/Abca1 to Inhibit Osteoclastogenesis and Bone Loss - Wang, Tingting; Mo, Lixia; Ou, Jiaxin; Fang, Qinghua; Wu, Huimei; Wu, Yuzhe; Nandakumar, Kutty Selva (Frontiers in Immunology, 2022)
Bone loss due to an increased osteoclast activity is common in osteoporosis and rheumatoid arthritis. For the first time, we observed an inhibition of osteoclast formation and bone resorption by OMVs from a Gram-negative, pathogenic bacterium, Proteus mirabilis (P.M). Gene ontogeny and KEGG enrichment analyses of miRNA and mRNA sequencing data demonstrated a significant effect of P.M OMVs on mitochondrial functions and apoptotic pathways. OMVs induced mitochondrial dysfunction through increased level of intracellular ROS, collapse of mitochondrial membrane potential (ΔΨm), and modulation of Bax, Bcl-2, caspase-3 and cytochrome c expression. In addition, P.M OMVs strongly inhibited miR-96-5p expression, which caused an up-regulation of ATP binding cassette subfamily A member 1 (Abca1) in osteoclasts leading to an increased level of mitochondria-dependent apoptosis. Moreover, treatment with P.M but not E. coli OMVs attenuated bone loss in experimental osteoporosis and collagen induced arthritis. Collectively, we demonstrated osteoprotective functions of OMVs from Proteus mirabilis, which down-regulated miR-96-5p causing increased Abca1 expression and mitochondria dependent apoptosis.